Simulation of SARS-CoV-2 Aerosol Emissions in the Infected Population and Resulting Airborne Exposures in Different Indoor Scenarios - Michael Riediker; Christian Monn (Aerosol and Air Quality Research)
Abstract Some of the SARS-CoV-2 virus can become airborne. Estimates suggest that the exhaled viral emissions from an infected person with high viral load can result in critical airborne concentrations in poorly ventilated small rooms. This project aimed to develop an indoor scenario simulator to rapidly assess the potential exposure in different indoor situations. It uses the estimates of a Monte Carlo simulation for the viral emission strength of breathing, speaking softly and loudly. The resulting emitter strength feeds a near-field far-field well-mixed room model. The indoor scenario simulator allows testing different room and ventilation sizes, wearing different masks, and different levels of physical activity and speech types for different percentiles of emitter strength in the population. The scenario tests suggest that in typical situations such as moderately ventilated offices, small shops, trains, buses, or carpool, very high emitters (99th percentile and above) not wearing masks are likely to cause concentrations with an elevated risk of infection via aerosols, especially in the near-field of the infected person. Speaking loudly and high levels of physical activity further increase the concentrations. If all persons wore surgical (hygiene) masks or filtering respirators with a higher protection factor, the expected concentrations were low in most situations, even if the viruses were released by “super-emitters” (top 1 permille emitter). This indoor scenario simulator may be helpful for decision makers as well as workplace and facility experts to assess and improve existing protection concepts, and to guide indoor exposure assessment campaigns.